1994
DOI: 10.1111/j.1399-3054.1994.tb02538.x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial associations between Daucus and nitrogen‐fixing Azotobacter cells in vitro

Abstract: Symbiotic associations were established between nitrogen‐fixing Azotobacter zettuovii (CRS‐H6) cells and carrot (Daucus carota L. cv. ‘Rother’ Half Long) tissues based on the induced carbon and energy dependency of diazotrophs on plant metabolic activity. Symbiotic associations were grown on nitrogen‐free media for four years. Plant regeneration was achieved from callus‐bacterium associations on nitrogen‐containing media. Light and electron micrographs are used to show the localization of bacteria in intercell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Due to this ability, we speculated that introduction of Z78 into the plant tissue culture system may benefit the host cells by accelerating and promote better embryoid formation. Several studies were also reported for in vitro Dancus-Azotobacter association (Varga et al, 1994), in vitro association of Strawberry-Azomonas (Preininger et al, 1997), and the most recent study of Crocus sativus Lplant growth promoting rhizobacteria (PGPR) interactions (Parray et al, 2015). However, no observation showed the role of bacteria and the interaction with tissue culture materials of oil palm in the early stage.…”
Section: Resultsmentioning
confidence: 99%
“…Due to this ability, we speculated that introduction of Z78 into the plant tissue culture system may benefit the host cells by accelerating and promote better embryoid formation. Several studies were also reported for in vitro Dancus-Azotobacter association (Varga et al, 1994), in vitro association of Strawberry-Azomonas (Preininger et al, 1997), and the most recent study of Crocus sativus Lplant growth promoting rhizobacteria (PGPR) interactions (Parray et al, 2015). However, no observation showed the role of bacteria and the interaction with tissue culture materials of oil palm in the early stage.…”
Section: Resultsmentioning
confidence: 99%
“…At an early stage, this relationship allows the host plant to be better adapted to the inoculum for an effective and efficient micropropagation process (Sturz et al, 2000;Azlin et al, 2007). Some early micropropagation stages of plant-microbe interactions have also been reported, such as Rhizobium japonicum associated with tobacco and cowpea cell cultures (Scowcroft and Gibson, 1975), Azotobacter zettuovii and carrot callus (Varga et al, 1994), Azomonas insignis with strawberry callus (Preininger et al, 1997), Azospirillum sp. and Gluconacetobacter sp.…”
Section: Artificial Symbiosis Of Pgpr and In Vitro Plant Culturementioning
confidence: 99%
“…Inoculated bacteria can eventually increase the availability of nutrients and phytohormones and reduce any potential biotic and abiotic plant stresses faced by plant tissue culture material. An artificial symbiosis between selected diazotrophic PGPR and in vitro plant materials is a viable solution for transferring the inoculum to newly selected hosts ( Varga et al., 1994 ). If the cultural conditions are refined, thus, a successful symbiotic relationship between plant cells and PGPR can be created ( Maksimov et al., 2011 ).…”
Section: Artificial Symbiosis Of Pgpr and In Vitro ...mentioning
confidence: 99%
See 1 more Smart Citation